Synthesis and Mechanical Properties of Novel Ni/PU Hybrid Foams: A New Economic Composite Material for Energy Absorbers1. Issue 4 (17th September 2015) - Jung, Anne; Diebels, Stefan
Abstract : Open‐cell Al foams electrocoated with nano‐Ni improve the energy absorption capacity in comparison to pure Al foams. Since Al foams are very expensive and as seen from micromechanical FE‐simulations that the most stress under loading is on the coating, in this contribution, polyurethane (PU) foams are electrocoated with nano‐Ni. The Ni/Al and the Ni/PU foams are compared regarding strength, energy absorption capacity, and costs using quasi‐static compression tests and digital image correlation. Compared to Ni/Al foams, the new Ni/PU foams provide only a third of the specific energy absorption capacity per density but they are largely superior in costs per absorbed amount of energy. Abstract : Ni/PU hybrid foams are a new class of highly economic cellular energy absorbers of a polyurethane (PU) substrate foam coated with nanocrystalline nickel. The Ni/PU hybrid foams have been prepared using electrochemical deposition. The mechanical properties are compared with Al and PU foams, as well as with Ni/Al hybrid foams.